Proposal the application of DMAIC tools and value stream mapping under the perspective of the lean philosophy for process improvement: a case study - de Souza Pinto, Jefferson (2017)
After a recent merger, the in vitro diagnostic equipment trade company in Brazil, study object, faces difficulties for its logistics flow. The work proposes the application of the DMAIC tools, contained in the context of the six sigma, and Value Stream Mapping (VSM) under the lean philosophy perspective in order to identify the focus of waste that can be improved, corroborating with lean thinking. Unlike the common application of VSM, used in manufacturing processes, this study has its application in a service chain. From the Methodology point of view, the case study uses a qualitative approach, having as strategy the bibliographics with a descriptive and explanatory objective. Additionally, it is delineated based on the DMAIC cycle to establish the industrial overview and method of conducting the process study, and consequently, the influence on the management by the guidelines and their impact on the management of the work routine. Thus, the VSM application is presented to control the flow of distributed inventory parts with the current and future process state maps. Finally, the analyzes show the results obtained with the reduction of the waste, from the centralization of the company's inventory.